Treatment of paraneoplastic neurological syndromes with antineuronal antibodies (Anti-Hu, Anti-Yo) with a combination of immunoglobulins, cyclophosphamide, and methylprednisolone. Issue 4 (1st April 2000) - Keime-Guibert, F; Graus, F; Fleury, A; René, R; Honnorat, J; Broet, P; Delattre, J-Y
Abstract : OBJECTIVES: To evaluate the effect of a combination of immunoglobulins (IVIg), cyclophosphamide (CTX), and methylprednisolone (MP) on the clinical course of patients with paraneoplastic neurological syndrome (PNS) and antineuronal antibodies (Abs). METHODS: Seventeen patients with paraneoplastic encephalomyelitis/sensory neuropathy (PEM/SN) with anti-Hu Abs (n=10) or cerebellar degeneration (PCD) with anti-Yo Abs (n=7) received one to nine cycles (mean 3.5) of a combination of IVIg (0.5 g/kg/day from days 1 to 5), CTX (600 mg/m2 at day 1) and MP (1g/day from day 1 to 3). The Rankin scale (RS) was used to evaluate the response. A positive response was considered as either improvement or stabilisation in patients who were still ambulatory (RS⩽3) at the onset of treatment, whereas only improvement, and not stabilisation, was considered a therapeutic benefit in bedridden patients (RS⩾4). RESULTS: Tolerance was good and no patient experienced grade 3/4 toxicity (World Health Organisation). Sixteen patients were evaluable for response. Of the seven patients with RS⩾4, none improved. Of the nine patients with RS⩽3, none improved but three (two SN and one PCD) stabilised for 4, 35, and 16 months. CONCLUSIONS: This study suggests that vigorous immunosuppressive treatment is not useful in severely disabled PNS patients with antineuronal Abs. In a minority of patients (mainly with SN) who are not severely disabled at the onset of treatment, a transient stabilisation is possible and deserves further evaluation.